Perbaikan Layout Mesin Produksi Longsong Munisi menggunakan Metode Systematic Layout Planning dan Blocplan (Studi Kasus : Divisi Munisi - PT. Pindad (Persero)) - Kustriyanto, Eddy; Pambuditama, Ishardita; Irawan, Yudy Surya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
Layout of the existing machines using cell system has been applied since 2005 and the machine operators have known the weaknesses, so it is necessary to improve the layout of the machines. This study was conducted to improve Â the machines layout cartridge case production by using Systematic Layout Planning and Blocplan with quantitative and qualitative considerations. The qualitative considerations are working ergonomies, while the quantitative considerations are the distance of product routing between one process with the next process and backtracking from product flow between workstations with another. A qualitative assessmen tends to be based on subjective considerations of each department facitity. Blocplan was the simple and practical method used in the settlement of this problem. Blocplan changed the layout by calculating the minimum total distance traversed in the movement of the materials between workstations. The application of Systematic Layout Planning methods and Blocplan in improving the layout and shortening production time in Hall OP decrease of product displacement distance is 26.77 meters (13.50%) i.e.: before the improvement Â was 198.36 meters, after improvement is 171.59 meters. Relayouting of the cell for improving the groups in the type of process and the machines also creates a higher state of comfortable working condition.